STUDI PENGAWETAN LARUTAN ENZIM BROMELIN KASAR SECARA FILTRASI DAN PENAMBAHAN NATRIUM BENZOAT: (Study Of Preservation Crude Bromelain Enzyme By Filtration And Addition Of Sodium Benzoate) - Nandi K Sukendar; Amran Laga; Try Permata Siade (jurnal1, 2018)
(Ananas comosus (L) Merr) is a plant that contains enzyme bromelin in the fruit, leaf and skin but more in the stem. In general, enzymes are produced and marketed in powder form. However, producing enzymes in powder form requires high process technology and very expensive cost. The purpose of this research were to know how to prepare bromelin enzyme in liquid form and it preservation technique, and to know the quality of bromelin enzyme during storage. This research was conducted through 3 stages: 1. Extraction of bromelin from pineapple stem, 2. Physical and Chemical preservation and 3. Observation of enzyme storage. The results of the study showed that preservation of enzyme bromelin physically and chemically still performed enzyme activity on day 32, while enzyme without preservation did not show activity at day 24. Bromelin enzyme with physical preservation was better than chemical preservation.